Online cooperative learning in communication and teamwork skills development - Ginaya, Gede; Somawati, Ni Putu; Mataram, I Gusti Agung Bagus (Journal of Applied Studies in Language, 2022)
The findings of several references reveal that most unemployed social science graduates have poor communication skills and collaborative skills. A revolutionary and visionary learning process is needed to improve the ability of graduates through vocational education that emphasizes practice rather than theory. A constructive learning environment with the application of cooperative learning strategies provides an active learning experience for students and simultaneously studies subjects. The group investigation-based learning structure is accompanied by the support of a learning management system (LMS) which aims to increase the effectiveness of learning and improve communication and collaborative skills. The implementation of online learning is improved by referring to the principles of e-learning. Learning management system interactive tools and other applications are provided for the needs of students in learning activities. This article also discusses the online learning syntax that supports the process of interaction and communication in the implementation of cooperative learning.